2020
DOI: 10.3390/su122410668
|View full text |Cite
|
Sign up to set email alerts
|

Co-Composting of Khat-Derived Biochar with Municipal Solid Waste: A Sustainable Practice of Waste Management

Abstract: Biochar is a way to improve the performance of the composting process and the quality of compost. This study was aimed to investigate the optimum ratio of khat straw (Catha edulis) biochar and organic municipal solid waste mixtures to improve the quality of the resulting co-composts. Khat-derived biochar during pyrolysis at 350 °C was added to organic municipal solid waste mix and four co-composting treatments were prepared with the compositions (% w/w): control compost (no biochar) and 5%, 15%, and 25% co-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
(89 reference statements)
2
3
0
Order By: Relevance
“…At the end of the composting process, the C content of the piles containing 15% and 25% biochar were measured as 19.38% d.m. and 21.45% d.m., respectively 3 , which is similar to the trend seen in the present study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…At the end of the composting process, the C content of the piles containing 15% and 25% biochar were measured as 19.38% d.m. and 21.45% d.m., respectively 3 , which is similar to the trend seen in the present study.…”
Section: Resultssupporting
confidence: 92%
“…In the cooling stage, mesophilic bacteria start to work again and in the last stage (compost maturation stage), actinomycetes, molds and some fungi appear 38 . Specifically, an excessive and continuous increase in temperature (typically more than 65 degrees Celsius), leads to a decrease in the population of beneficial microorganisms and, as a result, a decrease in the speed of the composting process 3 and a decrease in temperature leads to a decrease in the activity of effective microorganisms and the reduction of production efficiency will occur 18 . It is very necessary and vital that during the active stage of industrial composting, the temperature is kept within the range of activity of thermophilic bacteria so that pathogens and weed seeds are destroyed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were attributed to the rapid release of volatile compounds during pyrolysis at higher temperatures. The results obtained in this study align closely with previous research [12,57,69,70], which investigated the impact of pyrolysis temperature on biochar porosity and pore size using SEM and BET analysis simultaneously. It has been found that the pyrolysis reaction obtained in this study closely matches the results of Landrat et.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir) Characterizationsupporting
confidence: 90%
“…i.e i) control compost mix (no biochar), ii) 5% co-composted biochar (95%w/w organic waste mix + 5% w/w biochar), iii) 15 % co-composted biochar (85% w/w organic waste mix + 15% w/w biochar), iv) 25% co-composted biochar (75% w/w organic waste mix + 25% w/w biochar). The physico-chemical properties of amendments were showed in Table 1 30 .…”
Section: Description Of Organic Amendmentsmentioning
confidence: 99%